Preparation and characterization of Manganese doped iron oxide magnetic nanoparticles coated pine cone powder and its applications in water treatment - Ouma, Immaculate Linda Achiengꞌ (My University, 2019)
Trivalent arsenic (As(III)) and hexavalent chromium (Cr(VI)) toxicity have necessitated a great deal of research into the remediation of contaminated water. The techniques applied including oxidation, coagulation-flocculation and ion exchange have suffered drawbacks due to the high cost of materials and equipment, complex operations and secondary pollution among others. Adsorption, however, remains a cost-effective solution in the remediation of contaminated water. The use of biosorbent materials further lowers the cost of the adsorption process and improves its eco-friendliness. These biomaterials, however, suffer some drawbacks as poor porosity, low adsorption capacities and mechanical strength thus require modifications to improve their applicability as biosorbents. In this work pine cone powder, a waste from pine trees, was used as a biosorbent for the removal of As(III) and Cr(VI) from water. The powder was pre-treated with Fenton’s reagent to oxidize some of the functional groups and provide more binding sites. Iron oxide magnetic nanoparticles (magnetite) were incorporated into the pine cone matrix to form a magnetic composite with higher heavy metal affinity. The magnetite nanoparticles were also doped with manganese to improve their redox capacities and aid in the oxidation of the toxic As(III) to the less toxic As(V) and allow for improved binding. The adsorbents used in the study were therefore named as Fenton’s treated pine cone powder (FTP), pine cone -magnetite composite (FTP-MNP), magnetite nanoparticles (MNP), manganese doped magnetite nanoparticles (Mn MNP) and manganese doped pine cone-magnetite composite (Mn FTP-MNP). The prepared materials were fully characterized, and the adsorption process was optimized for both As(III) and Cr(VI) removal from aqueous solution. After modification the surface area of the particles increased in the order Mn MNP>MNP>Mn FTP-MNP>FTP-MNP>FTP. Surface and Xray analysis confirmed the formation of magnetite by the presence of both ferric and ferrous ion states on the surface and characteristic diffraction peaks for magnetite. The adsorption data was fitted into isotherm and kinetic models and the nature of adsorption was determined from the thermodynamic and kinetic parameters. Equilibrium studies indicated that the adsorption followed Langmuir isotherm for all adsorbents and was thus monolayer in nature, further analysis indicated that chemisorption was the predominant type of adsorption with ion exchange being the predominant mechanism of adsorption. Spent adsorbents were tested for reusability and displayed excellent adsorption capacities when used for up to three times. Adsorption mechanism was evaluated using characterization techniques and the ion-exchange mechanism inferred from thermodynamic data was confirmed spectroscopically with redox reactions aiding in the removal of the pollutants from water. The introduction of competing anions in solution, lowered the adsorption efficiency of both arsenic and chromium on the adsorbent indicating that there was competition for adsorption sites.
D. Tech (Department of Chemistry, Faculty of Applied and Computer Sciences) Vaal University of Technology.
Keywords: Iron, Manganese, water treatment, trivalent arsenic, hexavalent chromium, biosorbent material; Manganese.; Pine cones.; Nanoparticles -- Magnetic properties.; Water -- Purification.